PHILOSOPHICAL MEANING OF KLANA UDENG MASK MOVIE - Harahap, Rina Yanti; Sukerta, Pande Made; Soewarlan, Santosa (jfpublisher, 2023)
Nowadays, the traditional art of masks from Indramayu can still be found in various art forms, such as mask dance and mask puppetry. In its development, the art of mask tradition was adapted to the medium of film. When adapted into the medium of film, the mask dance performance art changes its function to become part of the educational media and part of the cultural tourism promotion in fulfilling the need to maintain the existence of the traditional art of masks to remain sustainable. This research aims to see the changes that occur and the meanings that arise from the traditional art adapted from mask dance into a movie entitled Klana Udeng Mask and identify the philosophical meanings in the movie. To comprehend the changes and meanings from the traditional art adapted from mask dance into a movie entitled Klana Udeng Mask, the researcher uses qualitative research using visual semiotics. In this research, the movie Klana Udeng Mask is interpreted with a semiotic approach from Roland Barthes. The movie Klana Udeng Mask has a philosophical meaning about gratitude and maintaining the relationship between humans and God Almighty. This philosophical meaning is evident in the opening scene of the mask dancers praying to God Almighty and the closing scene of them performing grateful praying movements to God Almighty. Changes in semiotic meaning in the Klana Udeng Mask movie affect the visual signs of the elements in the movie.